1993
DOI: 10.1897/1552-8618(1993)12[1193:amsafm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Mercury Saturation Assay for Measuring Metallothionein in Fish

Abstract: An accurate, rapid, sensitive, and simple method using mercury saturation for quantifying metallothionein (MT) is described. A complex solution ("pseudocytosol") of enzymatic and nonenzymatic thiols, including rabbit liver MT-11, and supernatants from homogenized samples of rainbow trout liver were incubated in the presence of '03Hg in 10% trichloroacetic acid Excess Hg was bound to and removed by chicken egg albumin, which denatured on contact with the acidic assay medium. After centrifugation, MT labeled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 22 publications
0
39
0
1
Order By: Relevance
“…2). The method was shown by Dutton et al (1993) to be simple, specific, and rapid; they demonstrated suecessful displacement of Cu (96% release), Zn, and Cd by Hg in trials with rainbow trout (Oncorhynchus my&s) hepatic MT, known to have a high Cu content. The characteristic overestimation of MT observed in the original method of Piotrowski et al (1973) was overcome by Dutton et al in the modified assay by adding an exogenous protein (egg albumin) to scavenge Hg bound to cytosolic ligands other than MT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The method was shown by Dutton et al (1993) to be simple, specific, and rapid; they demonstrated suecessful displacement of Cu (96% release), Zn, and Cd by Hg in trials with rainbow trout (Oncorhynchus my&s) hepatic MT, known to have a high Cu content. The characteristic overestimation of MT observed in the original method of Piotrowski et al (1973) was overcome by Dutton et al in the modified assay by adding an exogenous protein (egg albumin) to scavenge Hg bound to cytosolic ligands other than MT.…”
Section: Methodsmentioning
confidence: 99%
“…The Hg-saturation assay we used was adapted sliahtlv from that of Dutton et al (1993). Freshrat'hemoglobin was substituted for e& albumin as the exogenous protein; it formed firmer pellets on centrifugation, which facilitated withdrawal of the supernatant for y-counting.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal metal-MT stoichiometries of unknown biological significance have been sumption of a fully reduced MT pool binding metals in a definite stoichiometry has been the basis of several quantita-observed via in vitro saturation of apo-MT, both divalent Scheuhammer and Cherian, 1991). Thus, one likely Cd saturation mechanism would include (Scheuhammer and Cherian, 1991); Cd 2/ (Eaton and Cherian, 1991); and Hg 2/ (Dutton et al, 1993;Malley et al, the thiolic moieties of mercaptoethanol in the coordination structure (Fig. 6B).…”
Section: Fig 2 Hplc (Size Exclusion)-microatomization-aas Chromato-mentioning
confidence: 99%
“…Saturation techniques such as Cd(II) saturation method [25,26], Ag(I) [27,28], and Hg(II) saturation assays [29,30], followed by immunochemical [31][32][33][34][35][36], separation [21,22,24,[37][38][39], electromigration [40][41][42][43][44][45], and electrochemical techniques [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] are most frequently used for MT quantification in biological samples. Information about the expression and function of single MT isoforms can be found by mRNA analysis using RT-PCR or expression microarray [66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%